1994
DOI: 10.1002/bjs.1800811009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of intraoperative embolization detected by transcranial Doppler ultrasonography during carotid endarterectomy: A prospective study of 100 patients

Abstract: A study was performed to investigate the clinical significance of microembolization detected by transcranial Doppler ultrasonography (TCD) by determining the quantity and character of emboli and correlating these with neurological and psychometric outcome, fundoscopy, automated visual field testing and computed tomographic brain scans in 100 consecutive patients undergoing carotid endarterectomy. Embolization was detected in 92 per cent of successfully monitored operations. Most emboli were characteristic of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
4
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(127 citation statements)
references
References 14 publications
4
109
4
6
Order By: Relevance
“…Very high percentages (up to 95%) have been reported by several groups of investigators. 5,[7][8][9][10][11][12][13] Exclusion of the sonographic signals that occur at and immediately after declamping greatly reduces the overall rate of detected microemboli. In one study considering only emboli occurring at flow restoration, a rate as low as 5% was reported along with what were considered to be flow turbulence signals in 40% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very high percentages (up to 95%) have been reported by several groups of investigators. 5,[7][8][9][10][11][12][13] Exclusion of the sonographic signals that occur at and immediately after declamping greatly reduces the overall rate of detected microemboli. In one study considering only emboli occurring at flow restoration, a rate as low as 5% was reported along with what were considered to be flow turbulence signals in 40% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…5,[7][8][9][10][11][12][13] It has been suggested that increased cerebral microembolization may positively correlate with postoperative deterioration of cognitive function or the appearance of lacunar infarcts on MRI. 7,8 However, the clinical relevance of sonographic embolic signals remains unclear because most of them are not associated with focal neurological deficits. 14,15 Whether embolic signals represent an increased risk of postoperative silent brain ischemia also remains to be determined.…”
mentioning
confidence: 99%
“…6,9 Detection of MES during the exposure procedure has been shown to correlate with postoperative neurologic deficits immediately after CEA. [5][6][7][9][10][11] Several investigators have compared MES during the exposure procedure for the carotid arteries in CEA with histopathologic findings of excised carotid plaque and have demonstrated that development of the MES was strongly associated with vulnerable carotid plaques consisting primarily of intraplaque hemorrhage and/or intraluminal thrombus. 12,13 Intraplaque hemorrhage might cause formation of intraluminal thrombus likely due to chemical mediators, increased stenosis, or changes in eddy currents, though the associations among these remain unclear.…”
mentioning
confidence: 99%
“…A recent study suggested that normalization of cerebral metabolism via improvements in cerebral hemodynamics after CEA may result in cognitive improvement as well as functional recovery of the neurotransmitter system. 5) Other investigators have hypothesized that cognitive impairment after CEA may result from three possible mechanisms 2,[6][7][8][9][11][12][13]18) : cerebral hemispheric hypoperfusion during ICA clamping, intraoperative gaseous and particulate emboli from the surgical site, and postoperative cerebral hyperperfusion. The present study showed no relationship between duration of ICA clamping or new ischemic lesions on postoperative diffusion-weighted imaging and postoperative cognitive change.…”
Section: Discussionmentioning
confidence: 99%